(untitled) (IAHS Medical Journal, 2022)
Background: An outbreak of a COVID-19 pandemic disease, caused by a novel coronavirus SARS-CoV-2, has posed a serious threat to global human health. Bangladesh has also come under the attack of this viral disease. This work aimed to explore the educational status, the age group status, the socio-economic status, age and gender predisposition to COVID-19 vaccination program and to assess the knowledge, attitude vaccination status among the population of Anowara Upazilla, Chattogram and to identify the underlying causes associated with delayed and no vaccination and to find out the occurrence of adverse effect following immunization among the people. Materials and methods: A descriptive type of cross-sectional study was conducted. The sample size was 136. It was selected by non-probability type of purposive sampling technique. Data were collected on 11th November, 2021 by face-to-face interview from the respondent with the help of a prepared mixed questionnaire. Results: Among the respondents 59.56% population was immunized with COVID-19 vaccine and 40.44% population was not immunized with COVID-19 vaccine. 41.98% was male and 58.02% was female. Those who did not get vaccinated, the main reason was fear (About 36.36%).27.27% population didn’t get vaccinated because they were lactating mother or pregnant women, 10.91% of population had no NID/no birth certificate, 14.54% of population registered for vaccination but didn’t get the SMS and last but not the least about 10.91% population didn’t get vaccinated due to other personal causes. The population who were vaccinated, among them 93.83% didn’t face any problem but 6.17% population faced some problem while getting vaccinated. Population who didn’t get vaccinated, most of them were illiterate and of 18-27 years age group and those who were vaccinated of 28-37 years age group and literate. Conclusion: The main reason is not to take vaccine is the fear and wrong information about vaccine. Literacy rate has an influence on vaccination. This study will help people to get knowledge about COVID-19 vaccination programme and it will encourage them to take vaccine soon that will help them to lead a healthy life. IAHS Medical Journal Vol 4(2), December 2021; 55-59